DUPLICITY IN REGULATION AND PERFORMANCE OF THE FINANCIAL SECTOR IN KENYA - Ogada, Dr.Agnes (International Journal of Finance, 2021)
Purpose: The objective of the study was to investigate the duplicity in regulation and performance of the financial sector in Kenya. The specific objectives were; to review and identify regulation duplication/competition in existing regulatory framework for the financial sector in Kenya; to describe how regulatory effectiveness has been measured in empirical literature; to assess whether the current regulatory structure has affected the performance of the financial sector in Kenya and lastly to suggest potential ways of enhancing regulatory effectiveness in Kenya. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study found out that financial sector in Kenya and other developing economies have reported losses on a large scale due to under regulation and regulator duplicity. Some of these have become insolvent, or have had to be taken over or rescued by their governments. A single market regulator clearly has its own advantages over multiple regulators. But it is more suitable for well-developed and mature markets which are smaller in size, like the UK. The study also found out that Kenya's economy and political arena are not mature enough to handle a single financial market regulator. In this light it can be asserted that even mature economies such as the United States still have multiple regulators. Unique contribution to theory, practice and policy: Adherence to principles of open government, including transparency and participation in the regulatory process to ensure that regulation serves the public interest and is informed by the legitimate needs of those interested in and affected by regulation. Governments should ensure that regulations are comprehensible and clear and that parties can easily understand their rights and obligations. Organizations should create personalized technology systems that create a demand adaptation of ICT at every level of the organizational operations